Model Pemberdayaan UMKM melalui Intensifikasi dan Integrasi Sistem Komunikasi sebagai Dasar untuk Mempercepat Penguatan pada K - S., Fathor A. (Jurnal Aplikasi Manajemen, 2014)
The purposes of this research are, 1). Analyze the environment (internal and external) of SME's strategic center to determine the strengths and threats that will be used as the substance of the communication, 2). Determine the parameters of performance of SME's areas as a reference for determining the relevant form of communication, and 3). Formulate a model empowerment of SME's industrial centers batik through communication programs in a more intensive and integrated with the local government in an effort to increase institutional power. The population was batik craft industry SME's in Bangkalan Regency. This study used a survey method. The number of samples as much as 145 respondents. Strategic environmental analysis was done using a SWOT analysis and multiple regression analysis. SWOT analysis result obtained value of 1,38 to internal factors and the value of 2,23 to external factors. The final value said to be a grand strategy. That value indicates the system of communication of the central group has properties aggressive which need to be developed through the creation of strategy that prioritizes the power possessed by the SME's to take advantage of the opportunities that exist. Whereas the results of the regression analysis showed that some of the variables analyzed, variable market conditions were the most influential variables on performance of SME's businesses.